Clonal Progression during the T Cell-Dependent B Cell Antibody Response Depends on the Immunoglobulin DH Gene Segment Repertoire - Trad, Ahmad; Tanasa, Radu Iulian; Lange, Hans; Zemlin, Michael; Schroeder, Harry W.; Lemke, Hilmar (Frontiers in Immunology, 2014)
The diversity of the third complementarity determining region of the IgH chain is constrained by natural selection of immunoglobulin diversity (DH) sequence. To test the functional significance of this constraint in the context of thymus-dependent (TD) immune responses, we immunized BALB/c mice with WT or altered DH sequence with 2-phenyloxazolone-coupled chicken serum albumin (phOx-CSA). We chose this antigen because studies of the humoral immune response to the hapten phOx were instrumental in the development of the current theoretical framework on which our understanding of the forces driving TD responses is based. To allow direct comparison, we used the classic approach of generating monoclonal Ab (mAb) from various stages of the immune response to phOx to assess the effect of changing the sequence of the DH on clonal expansion, class switching, and affinity maturation, which are hallmarks of TD responses. Compared to WT, TD-induced humoral IgM as well as IgG antibody production in the D-altered ΔD-DμFS and ΔD-iD strains were significantly reduced. An increased prevalence of IgM-producing hybridomas from late primary, secondary, and tertiary memory responses suggested either impaired class switch recombination (CSR) or impaired clonal expansion of class switched B cells with phOx reactivity. Neither of the D-altered strains demonstrated the restriction in the VH/VL repertoire, the elimination of VH1 family-encoded antibodies, the focusing of the distribution of CDR-H3 lengths, or the selection for the normally dominant Ox1 clonotype, which all are hallmarks of the anti-phOx response in WT mice. These changes in clonal selection and expansion, as well as CSR indicate that the genetic constitution of the DH locus, which has been selected by evolution, can strongly influence the functional outcome of a TD humoral response.